Modulation versus Templating: Fine‐Tuning of Hierarchally Porous PCN‐250 Using Fatty Acids To Engineer Guest Adsorption. Issue 36 (1st August 2019) - Kirchon, Angelo; Li, Jialuo; Xia, Fangqing; Day, Gregory S.; Becker, Benjamin; Chen, Wenmiao; Sue, Hung‐Jue; Fang, Yu; Zhou, Hong‐Cai
Abstract: Modulation and templating are two synthetic techniques that have garnered significant attention over the last several years for the preparation of hierarchically porous metal–organic frameworks (HP‐MOFs). In this study, by using fatty acids with different lengths and concentrations as dual‐functional modulators/templates, we were able to obtain HP‐MOFs with tunable mesopores that exhibit different pore diameters and locations. We found that the length and concentration of the fatty acids can determine if micelle formation occurs, which in turn dictates the porosity of the resulting HP‐MOFs. The HP‐MOFs with different mesopores differed in their performance in gas uptake and dye adsorption, and the structure–performance relationships were ascribed to the pore diameters and locations. This approach could provide a potentially universal method to efficiently introduce hierarchal mesopores into existing microporous MOF adsorbents with tunable properties. Abstract : Best of both worlds : Fatty acids were used as dual‐functional modulators/templates to form hierarchically porous metal–organic frameworks (HP‐MOFs). The length and concentration of the fatty acid determined whether micelle formation could occur, and thus the porosity of the resulting HP‐MOF (see picture). HP‐MOFs with different mesopores differed in their performance in gas uptake and dye adsorption, which was ascribed to the diameter and location of the pores.